Strategies to Productively Reincorporate the Formerly-Incarcerated into Communities: A Review of the Literature - Jennifer Doleac (Institute of Labor Economics (IZA), 2018)
Two-thirds of those released from prison in the United States will be re-arrested within three years, creating an incarceration cycle that is detrimental to individuals, families, and communities. There is tremendous public interest in ending this cycle, and public policies can help or hinder the reintegration of those released from jail and prison. This review summarizes the rigorous evidence on the effectiveness of programs that aim to improve the reintegration and rehabilitation of the formerly-incarcerated. While there is a need for much more research on this topic, the existing evidence provides some useful guidance for decision-makers. The importance of evaluating existing and new strategies is also discussed.
Keywords: K42; J24; H76; I0; 330; prisoner reentry; employment; recidivism